Etnobotânica de plantas medicinais comercializadas em mercados públicos do nordeste brasileiro - Vieira, Vanessa Maria de Souza Fernandes (2012)
According to the World Health Organization, traditional medicine is the sum of personal experiences of a culture resorted to prevent, treat and cure physical and mental diseases. In northeastern Brazil, the use of medicinal plants as a therapeutic practice is diffusely present. In this context, public markets shelter herbalists, guiding the use and preparation plant, conserving the oral transmission. The Ethnobotany arises as a mediator between scientific and traditional discourses involving the cultural factor and its interpretation. The aim was to investigate the popular and traditional practices of medicinal plants using commercialized in three public markets in Northeast Brazil. It was characterized as observational, descriptive and exploratory, held in São Sebastião (CE), Central (PB) and São José (PE) markets in the period from February to August 2011. It was applied a questionnaire addressing socioeconomic issues on the trade of plants and information about each species sold. 33 participants registered herbalists, of whom 57.6% were female (n = 19), 24.2% were older than 60 years old and 96.9% were born in the Northeast (n = 32). Regarding education, 42.4% completed high school (n = 14). They sold an average of 40 units per day, and getting less than the minimum monthly wage by 28.5% of cases (n = 6), among those who answered this question. The average working time in this job was 16 years. Used as a source of knowledge the interpersonal relationships 37% (n = 29) and 9.63% have attended some training on the management of medicinal plants (n = 3). Of the species mentioned (n = 311), came to the number of 43 matching the three markets. We calculated the relative importance (RI), and the most outstanding plants: rosemary (RI = 1.87); jatobá (RI = 1.72) and eucalyptus (RI = 1.44). After botanical identification of the material-witness, it was confirmed the nomination popular to rosemary (Rosmarinus officinalis L.). The samples provided by middlemen jatobá Central Market, PB, were infertile, precluding accurate identification (Hymenaea courbaril aff.). The samples from Ceara and Pernambuco were identified as Hymenea stignocarpa Hayde. The Eucalyptus was sold, which, according to scientific literature should be used as a household disinfectant. It was also observed, the Informant Consensus Factor (ICF), and treatment for disorders of the respiratory system the most prevalent (ICF = 0.65), with 64 species listed and 17 different types of uses reported. The absence of group activities affect the quality of that office, putting at risk the health of the population that uses the herbalists hoping the cure for their ills. The educational workshops on the proper use of medicinal plants could qualify these professionals, stimulate the entry of more people in this activity and (re)gain the recognition of Brazilian society practices of popular and traditional use of medicinal plants.